Learning modern foreign languages in the Republic of Ireland : a study of the learning experiences of upper-secondary level students - Minton, Patricia (Trinity College (Dublin, Ireland). School of Education, 2012)
This study investigates the learning experiences of upper-secondary level students in the Republic of Ireland whilst learning modern foreign languages at school. Essentially this study has sought to capture the students’ voice. It is a snapshot in time of the learning experiences of upper-secondary level students. An initial analysis of European educational policy in modern foreign languages education has shown how the period from the European White Paper on Education in 1995 marked a time of greater consultation and investment in modern foreign languages in European education. Thus, in the evaluation phase of this project, questionnaire data from 732 non-sixth year senior cycle students were obtained to provide an understanding of government commitment to the realisation of the Council of Europe policy of 'mother tongue plus two foreign languages' before the end of compulsory schooling in Ireland - determined in this study by (i) the provision, uptake and retention of modern foreign language subjects in secondary education; (ii) the current situation regarding grade achievement in state examinations in modern foreign language subjects at school; (iii) the development of levels of fluency and proficiency in modern foreign languages at school; (iv) provision for ‘prior knowledge’ and ‘language and linguistic awareness’ in modern foreign language study at school; and (v) student motivation and learning strategies in the pursuit of learning modern foreign languages at school.
Keywords: Education, Ph.D.; Ph.D. Trinity College Dublin